Preparation of polymer/cholesteric liquid crystals composite films with broadband reflective capability from a polymerizable chiral dopant end-capped with menthyl group. Issue 1 (13th April 2023) - Zhang, Huimin; Li, Fei; Zhao, Yang; Zhao, Yuzhen; Gao, Jianjing; Zhao, Xiangrong; Miao, Zongcheng
Abstract: In this study, a polymerizable chiral dopant end-capped with menthyl group was synthesized. The solubility of the polymerizable chiral dopant in a mesogenic host was also studied. The film with left-handed broadband reflective capability was prepared via employing the chiral dopant and a bifunctional mesogenic compound as the polymerizable monomers. To enhance the reflection of the broadband reflective film, two films that reflected left-handed circularly polarized light and right-handed circularly polarized light, respectively, were superimposed to obtain a composite film. The reflection of the composite film for the light with the wavelength between about 800 and 1150 can exceed 60%.